Menu rahmah survey in Malaysia - Azmi, Muhammad Danial Iman; Mohd@Abd Rahman, Muhammad Faeez; Shahrin, Muhammad Irfan Farhan; Azahar, Khairul Azman Shah; Ahmad, Nur Intan Syafinaz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
January 2023, KPDN has launched the Menu Rahmah Program in partnership with strategic partners Food Shop Operators (Cooking) and the Association of Restaurant and Food Stall Operators. Participants in the Menu Rahmah Programme have committed to providing daily meals (lunch or dinner) for a price that does not exceed RM 5 per meal. The meals in the Menu Rahmah Program typically include one type of vegetable and either chicken or fish as the protein component. As Menu Rahmah grows in popularity and becomes a key part of Malaysia's social welfare initiatives, its execution, impact, and efficacy must be evaluated. Understanding the opinions and experiences of both consumers and stakeholders can provide useful insights into improving project outcomes and addressing potential issues. Therefore, studied have been done to collect detailed information on the experiences, views, and issues associated with Menu Rahmah. From the studies, most of the respondents agree and satisfied with the Menu Rahmah that is launch by the government. Almost all respondents agree that Menu Rahmah are very helpful in reducing their financial burden. In conclusion, Menu Rahmah is one of the good initiative launch by the government to help Malaysian people reduce their financial problem and government should oblige all food stall around Malaysia to provide at least one Menu Rahmah in their menu.